If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 1) = 4(x + 2) Reorder the terms: 6(1 + x) = 4(x + 2) (1 * 6 + x * 6) = 4(x + 2) (6 + 6x) = 4(x + 2) Reorder the terms: 6 + 6x = 4(2 + x) 6 + 6x = (2 * 4 + x * 4) 6 + 6x = (8 + 4x) Solving 6 + 6x = 8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 6x + -4x = 8 + 4x + -4x Combine like terms: 6x + -4x = 2x 6 + 2x = 8 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + 2x = 8 + 0 6 + 2x = 8 Add '-6' to each side of the equation. 6 + -6 + 2x = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 8 + -6 2x = 8 + -6 Combine like terms: 8 + -6 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 4x-6=8x-78 | | 6+5i= | | 4(x+3)=7(x-3) | | x+.2*x=16.8 | | 6(x-7)=11(x+8) | | 3(-4.363636364)-6y=-18 | | 4y-8=12y+40 | | -5x=-89 | | m^2+20m+100=0 | | 18-3x=5x+8 | | m^2+16m+60=0 | | 288=-66x | | 5x-45=60 | | 179.2/56 | | 4t=1.2 | | a-17=-15 | | y=0.1x+0.3 | | 7t=70 | | 34=2y+17 | | 9+5x=5x-4 | | 4(x-3)=7(x+3) | | (2w-4y-5)(5w+3)= | | 6x+12(0)=7 | | 2x-(7x-3)=20 | | 5-3(x-2)=x | | x+18=-37 | | 181/2+(-74/8) | | (3x+7)=(6x+2) | | -9(0)-4y=36 | | 25=-0.5(t^2)3.7+100 | | 8-5x=5-3x | | 2y-9=13y+79 |